ANALISIS PENGARUH STRUKTUR DEWAN KOMISARIS, STRUKTUR KEPEMILIKAN SAHAMDAN KOMITE AUDIT TERHADAP FINANCIAL DISTRESS - Ariesta, Dwiki Ryno; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
This study aim to examine the effect of the board structure, ownership structure and auditcommittee on financial distress. The structure of the board is measured by the proportion ofindependent commissioners, the ownership structure is measured by ownership of directors,ownership of commissioners and outside blockholders, while the audit committee is measured bythe audit committee independence. This study use a control variable is the size of the company.The population in this study is manufacture company listed on the Indonesia StockExchange in 2008-2010. Based on purposive sampling method, obtained 96 samples consisting of18 financial distress samples and 78 non financial distress samples. The criteria of financialdistress in this study is deficit equity company (negative equity) and / or get disclaimer opinionsfrom auditor. Data analysis using regression logistic by SPPS program.The results showed that the proportion of independent commissioners and audit committeeindependence have a significant effect on financial distress. While ownership of directors,ownership of commissioners and outside blockholders have no effect on financial distress.